Variations in the Two-Step Norm Elicitation Procedure - Plaß, Sabrina
The two-step norm elicitation procedure describes a commonly used tool for measuring normative expectations in an incentivized way. This study tests some of its design features to determine whether elicited beliefs and related behaviours vary depending on i) the time of elicitation (before vs after the decision), ii) incentivizing vs not incentivizing a question about normative expectations, and iii) questioning subjects on their beliefs about the action of interest alone or combined with an alternative action. An online experiment is conducted via Prolific comprising a dictator game and the elicitation of fairness beliefs. A pretest reveals that applying role uncertainty does not alter beliefs and behaviours compared to a baseline treatment without it. Subsequently, three treatments are implemented. Contrary to previous studies, results indicate that varying the time of elicitation does not significantly alter the money-share decision. However, incentivizing the question about normative expectations significantly increases the fit with the actual majority norm. Finally, asking about a fair share and an unfair share instead of only about fair sharing does not alter personal normative beliefs or normative expectations, but it increases the empirical expectations that other dictators have provided a fair share.
Keywords: Social Norms; Normative Expectations; Elicitation; Economic Experiment

Do Energy-Saving Nudges Deliver During High-Price Periods? Field Experimental Evidence From the European Energy Crisis - Tinnefeld, Vicky; Kesternich, Martin; Werthschulte, Madeline
Urged by the European Energy Crisis and the threatening consequences of severe natural gas shortages, energy providers launched gas-saving initiatives incor- porating financial incentives to reduce residential natural gas consumption. In collaboration with one of Germany’s largest energy providers, we conducted a natural field experiment (N = 2,598) to evaluate the effectiveness of a behaviorally-guided co-design of such a gas-saving initiative by implementing two established behavioral instruments – reminders of gas saving intentions and descriptive norm feedback. Our findings show limited effectiveness of the behav- ioral instruments during the high-price period. The feedback risks a “boomerang effect” among households with above-average initial savings, who reduce their conservation efforts in response. The reminder does not significantly enhance sav- ings in our main specifications, yet, realizes 1 percentage point savings in alternate models refining for outliers. Potential mechanisms include a significant intention- action gap and misperceived effectiveness of energy-saving actions, which are not alleviated by the reminder.
Keywords: Residential energy savings; energy crisis; behavioral interventions; survey data; field experiment

Transporting behavioral insights to low-income households: A field experiment on energy efficiency investments - Kesternich, Martin; Chlond , Bettina; Goeschl, Timo; Werthschulte, Madeline
Many industrialized countries have recognized the need to mitigate energy cost increases faced by low-income households by fostering the adoption of energy-efficient technologies. How to meet this need is an open question, but “behavioral insights” are likely components of future policy designs. Applying well-established behavioral insights to low-income house- holds raises questions of transportability as they are typically underrepresented in the existing evidence base. We illustrate this problem by conducting a randomized field experiment on scalable, low-cost design elements to improve program take-up in one of the world’s largest en- ergy efficiency assistance programs. Observing investment decisions of over 1,800 low-income households in Germany’s “Refrigerator Replacement Program”, we find that the transportabil- ity problem is real and consequential: First, the most effective policy design would not have been chosen based on existing behavioral insights. Second, design elements favored by these insights either prove ineffective or even backfire, violating ‘do no harm’ principles of policy advice. Systematic testing remains crucial for addressing the transportability problem, partic- ularly for policies targeting vulnerable groups.
Keywords: Transportability; low-income households; field experiment; randomized controlled trial; governmental welfare programs; energy efficiency; technology adoption

Multiple Normative Expectations and Interventions -Experimental Evidence on Whistleblowing Behaviour - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina
Normative expectations – beliefs about what others perceive as appropriate – have been shown to influence behavioural choices across various domains. We examine this concept in the context of whistleblowing, where potential whistleblowers face two competing norms: promoting fairness by reporting wrongdoing versus maintaining loyalty to peers by staying silent. We investigate how normative expectations about these two mutually exclusive actions affect reporting decisions. Specifically, we test whether providing information on the majority beliefs about either the appropriateness of whistleblowing, or of staying silent, or about both behaviours together, differentially affects the whistleblowing decision. Using an incentivized experiment with UK employees on Prolific, our study yields four key findings: First, employees are more likely to report misconduct when they believe that the majority considers whistleblowing to be appropriate. Second, they are less likely to blow the whistle when they believe staying silent is deemed appropriate. Third, this effect prevails for a particularly important subgroup: among employees who believe that the majority supports whistleblowing, the reporting probability increases substantially when they simultaneously expect that staying silent is deemed inappropriate. Fourth, providing information about both normative dimensions combined or only about the inappropriateness of staying silent significantly increases whistleblowing compared to the (no information) baseline and to information about whistleblowing appropriateness alone. These findings demonstrate the importance of normative expectations about both behavioural options for accurately predicting whistleblowing behaviour, and that social information interventions are most effective when they target behaviours where appropriateness beliefs about conflicting options are dispersed.
Keywords: Whistleblowing; Normative Expectations; Social Information Intervention; Social Norms; Economic Experiment

The Bot Delusion. Large language models and anticipated consequences for academics’ publication and citation behavior - Wieczorek, Oliver; Steinhardt, Isabel; Schmidt, Rebecca; Mauermeister, Sylvi; Schneijderberg, Christian (Futures)
The present paper discusses the extent to which Large Language Models (LLMs) may affect the scientific enterprise, reinforcing or mitigating existing structural inequalities expressed by the Matthew Effect and introducing a “bot delusion” in academia. In a theory-led thought experiment, we first focus on the academic publication and citation system and develop three scenarios of the anticipated consequences of using LLMs: reproducing content and status quo (Scenario 1), enabling content coherence evaluation (Scenario 2) and content evaluation (Scenario 3). Second, we discuss the interaction between the use of LLMs and academic (counter)norms for citation selection and their impact on the publication and citation system. Finally, we introduce communal counter-norms to capture academics’ loyal citation behavior and develop three future scenarios that academia may face when LLMs are widely used in the research process, namely status quo future of science, mixed-access future, and open science future.
Keywords: Large Language Models; Matthew Effect; Academic Publishing and Citation Systems; Scientific Norms; Thought Experiment

Collective Minimum Contributions to Counteract the Ratchet Effect in the Voluntary Provision of Public Goods - Alt, Marius; Kesternich, Martin; Gallier, Carlo; Sturm, Bodo (Journal of Environmental Economics and Management)
We experimentally test a theoretically promising amendment to the ratchet-up mechanism of the Paris Agreement. The ratchet-up mechanism prescribes that parties’ commitments to the global response to climate change cannot decrease over time, and our results show that its effect is detrimental. We design a public goods game to study whether cooperation is promoted by an amendment to the mechanism that stipulates that all agents must contribute at least a collectively chosen minimum based on the principle of the lowest common denominator. We find that binding collective minimum contributions improve the effectiveness of the ratchet-up mechanism. Non-binding minimum contributions, by contrast, do not encourage cooperation. Our data indicate that the difference is attributable to conditional cooperative dynamics. If other participants contribute less than the collective minimum contribution, even initially cooperative participants start to negatively reciprocate this form of non-compliance by contributing less.
Keywords: global public goods; climate change; institutions; ratchet-up mechanism; minimum contributions; laboratory experiment

Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Depicting the confrontation with anomalous data in Models of Data - Pollmeier, Pascal; Fechner, Sabine (15th Conference of The European Science Education Research Association (ESERA))
Keywords: Daten; anomale Daten; Auswertung; Umgang mit Daten; Experiment

Does augmented reality help to understand chemical phenomena during hands-on experiments?–Implications for cognitive load and learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure

Epistemological enhancement through confrontation with anomalous data - Pollmeier, Pascal
Keywords: Epistemologie; Mentale Modelle; Daten; Auswertung; Experiment

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Augmented reality in informal learning environments: A field experiment in a mathematics exhibition - Sommerauer, Peter; Müller, Oliver (Computers and Education)
Keywords: Augmented reality; Cognitive theory of multimedia learning; Field experiment; Informal learning; Museum